Entomofaunal diversity of Lepidoptera in different ecosystems of South India - M. Sakthi Saravana Bavan; C.Sundaravadivel; S.Lingathurai (Revista Electronica de Veterinaria, 2024)
Insect biodiversity is a type of biodiversity that solely focus on insect percentage because they are the most species-diverse group on Earth and play an important role in Ecosystem.  This study documents Entomofaunal Biodiversity of Lepidoptera in different Ecosystem in Southern district of Tamilnadu.  Insects collecting were carried out once in every fortnight from microhabitats such as arboreal litter, aerial, bark and boulder bed microhabitats using the collection tools, sweep net, beating sheets and light traps.  More than a different species of insects in  different ecosystems of Tamilnadu.  A total 16739 individuals insects were collected by three ecosystems.  Udangudi agro ecosystem (AES) represented with highest number of insects individuals 7238 followed by Keela vallanadu Scrub jungle ecosystem with 5428 number of insect individuals and Pudukottai Semi-arid ecosystem with 4073 number of insects individuals.  A total 17 families and 45 species are identified.  With this different ecosystems studied and analyzed with Dominance Index, Simpson Index, Shannon Index, Menhinick Index and Margalef Richness Index.  This will ensures sustainable entomological diversity of increasing the role of biological control in pest management systems.AES – Agro EcosystemSAES – Semi-Arid EcosystemSJES – Scrub-Jungle Ecosystem